Optically transparent melamine-formaldehyde polymers modified with proton acceptors - Lebedev, V.V.; Blank, T.A.; Avramenko, V.L.; Eksperiandova, L.P.; Mishurov, D.A.; Titskaya, V.D.; Shadrikov, A.S. (Functional Materials, 2009)
Investigation of reaction water binding in melamine-formaldehyde polymers with proton accepting compounds has shown that the use of dimethyl sulfoxide in 1/1 (v/v) ratio provides preparation of optically transparent materials. Introduction of dimethyl formamide and dimethyl sulfoxide improves the main characteristics of the material, but modification with dimethyl formamide reduces the polymer transparency.